Self-Management and Its Relationship with the Level of Job Satisfaction among Physical Education Teachers in the Center of Al-Diwaniyah Governorate - Atheer Elan Abdulhussein (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
The present study aimed to identify the level of self-management and the level of job satisfaction among physical education teachers in the center of Al-Diwaniyah Governorate, as well as to examine the nature of the relationship between the two variables. The researcher adopted the descriptive method using the correlational approach, as it is appropriate for the nature and objectives of the study. The research population consisted of physical education teachers working in schools in the center of Al-Diwaniyah Governorate. The research sample included (90) teachers, selected using an appropriate sampling method. Two research instruments were used: the Self-Management Scale and the Job Satisfaction Scale, each consisting of (30) items based on a five-point Likert scale. The psychometric properties of both scales, including validity and reliability, were verified prior to application. The results indicated that physical education teachers possess a high level of self-management and a moderate to high level of job satisfaction, as the calculated means were higher than the hypothetical means with statistically significant differences. The results also revealed a positive statistically significant correlation between self-management and job satisfaction, with a correlation coefficient of (r = 0.53) at a significance level of (0.01). This indicates that higher levels of self-management contribute to increased job satisfaction among physical education teachers. In light of the findings, the researcher recommended paying greater attention to developing self-management skills among physical education teachers through training and counseling programs, due to their positive impact on job satisfaction, professional performance, and the quality of the educational process.